Analysis of Instagram Social Media Usage on Public Perception of the Palestinian Refugee Issue - M. Angkasa Dharu; Muhammad Mafruh; Ahmad In'am Kholifi; Rian Hari Ramadhan; Rio Kurniawan (Penerbit Hellow Pustaka, 2026)
Social media, particularly Instagram, has become a primary means of voicing various social and humanitarian issues, including the conflict in Palestine. This study aims to analyze the influence of Instagram use on public perception of the Palestinian refugee issue. A quantitative approach was used, using a survey method with 35 respondents aged 18–35 who actively use Instagram and are exposed to content related to the Palestinian issue. Data were analyzed using validity, reliability, and normality tests, simple linear regression, and other classical assumption tests such as heteroscedasticity, multicollinearity, autocorrelation, t-tests, and F-tests. The results indicate a significant relationship between Instagram use and the formation of public perception of the Palestinian refugee issue (r = 0.623; p < 0.05). The regression model proved significant both simultaneously (F = 20.924; p < 0.05) and partially (t = 4.574; p < 0.05). These findings reinforce the role of visual social media in shaping public opinion and increasing empathy and public participation in global humanitarian issues.